2022
DOI: 10.1177/15480518221097278
|View full text |Cite
|
Sign up to set email alerts
|

How to Cope with an Abusive Leader? Examinations of Subordinates’ Affective Reactions, CWB-O and Turnover Intentions

Abstract: When subordinates experience abusive supervision, they often respond with “fight” (e.g., organizationally-directed counterproductive work behavior: CWB-O) or “flight” reactions (e.g., turnover intentions). Drawing on cognitive appraisal theory, we propose that negative (NA) and positive affect (PA) explain these distinct responses and that coworker emotional support differentially moderates the relationships of affective states with CWB-O and turnover intention. That is, we expect that emotional support exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…It reveals the differential influences of PA/NA on PB related to PR ( 21 ). That is, college students' PR might increase PB by reducing NA and increasing PA. NA strengthens counterproductive work behavior ( 87 ), like violating PB in the COVID-19 pandemic, and meanwhile negatively affects health behavior ( 88 ). Individuals with higher levels of PA are more likely to care for themselves ( 89 ) and show great potential in health behavior learning ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…It reveals the differential influences of PA/NA on PB related to PR ( 21 ). That is, college students' PR might increase PB by reducing NA and increasing PA. NA strengthens counterproductive work behavior ( 87 ), like violating PB in the COVID-19 pandemic, and meanwhile negatively affects health behavior ( 88 ). Individuals with higher levels of PA are more likely to care for themselves ( 89 ) and show great potential in health behavior learning ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by proposing and examining the positive relationship of abusive supervision with subordinates’ CCB, the current study enriched people’s understanding of how subordinates react to abusive supervision. Previous literature has shown that abusive supervision is negatively related to organizational citizenship behaviors (OCB; [ 33 ]), but fewer studies have noted that abusive supervision also makes subordinates engage in organizational citizenship behaviors against their will [ 22 ]. Our study empirically supported this relationship and found that subordinates’ fear of external threats strengthened the positive relationship between abusive supervision and CCB.…”
Section: Discussionmentioning
confidence: 99%
“…The current study adopts a 3-wave prospective study design because appropriate time lags may help reduce common method problems [ 21 ]. In accordance with previous studies (e.g., [ 33 , 47 ]), we chose one month as the interval. If the time lag is too short, it cannot reduce the salience of the predictor variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might intervene between supervisor frustration and abusive supervision. In this study, we reposition coworker support from the perspective of supervisors, which is missed by contemporary researchers (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%